Simulation and Analysis of Static Temperature Characteristics of 4H-SiC MOSFET - Liang ZENG; Cuixia WANG; Jiangfeng WU; Youling YU; Chengzhan LI; Xing DU (机车电传动)
SiC materials have excellent properties such as large forbidden band width, high critical electric field, high carrier saturation drift speed and high thermal conductivity, making them widely used in high temperature, high voltage, high power and other fields. In order to investigate the influence of temperature on the static characteristics of 4H-SiC MOSFET to guide the design and manufacture of 4H-SiC MOSFET in high temperature and high voltage environment, a high-voltage 4H-SiC MOSFET device was simulated and modeled based on the Silvaco platform, and the breakdown voltage, transfer characteristics and output characteristics at different temperatures were obtained. The influence of temperature on its breakdown voltage, threshold voltage, saturated current and on-resistance was investigated. The cell structure model of SiC MOSFET device with a breakdown voltage of 4 450 V at 300 K was obtained. It was verified that the static characteristics and parameters were affected by temperature. The influence law was consistent with the static characteristic theory of SiC MOSFET.